Draft Five Year Plan 1978-83 Road Transport - Planning Commission (Planning Commission, 1978)
Madhya Pradesh is the biggest State in area in the country, sprawling over a vast area but is poorly served by the Rail communication, Road Transport is, there fore, the only important factor for development of backward areas of Madhya Pradesh. Moreover, the State of Madhya Pradesh is situated in the heart of the country touching seven states 4% Orissa, Bihar, Rajasthan, Andhra Pradesh, Uttar Pradesh, Maharashtra and Gujarat, Accordingly the MPSRTC being a Public Transport has a great role to play.
Government of Madhya Bharat
Government of Madhya Pradesh Planning, Economics & Statistics Department
Keywords: Madhya Pradesh State plan; Road Transport Corporation; Replacement of vehicles; Training to conductor Drivers; Construction of Depots & Workshop Buildings; Central workshop where major repairs; Reconditioning of assemblies and renovation of bodies; According to DRF regulations; the expenditure; Employees working in the Corporation; Civil Engineering Department